2020
DOI: 10.1155/2020/3189672
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Activities of Ethanolic Extract Root of Ageratum conyzoides on Alloxan-Induced Cardiotoxicity in Diabetic Rats

Abstract: Diabetes mellitus has developed into one of the debilitating diseases disturbing the health of many people living with cardiovascular diseases in modern times. The root of Ageratum conyzoides was investigated for its effects on alloxan-induced diabetic Wistar rats’ cardiac tissues. Thirty-two (32) Wistar rats weighing between 180 and 190 g were randomly divided into four groups. The animals in groups B-D were induced with a single dose of 150 mg/kg body weight of alloxan (ALX) intraperitoneally. They were conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, administration of GAME and GAWE is highly effective in preventing tissue damage by reducing alteration of heart and bone tissues. These results are consistent with previously reported studies that supplementation of herbal flavonoids and polyphenols to diabetes-induced heart damage improved and minimized cardiac injury [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, administration of GAME and GAWE is highly effective in preventing tissue damage by reducing alteration of heart and bone tissues. These results are consistent with previously reported studies that supplementation of herbal flavonoids and polyphenols to diabetes-induced heart damage improved and minimized cardiac injury [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…cTnI is considered as one of the most sensitive and commonly used biomarkers, and its release from the cardiomyocytes is proportional to the size and extent of cardiac tissue injury [28]. It has been reported by Robertson et al, (2004); Goyal and Patel, (2011) that the cytotoxic action of alloxan is mediated by the formation of free radicals such as superoxide and catalase radicals, which selectively damages the β cells of the pancreas, which are known to be one of the weakest structures to oxidative stress by generating excess reactive oxygen species and produces heart lesions that are similar to human diabetic cardiomyopathy [29]. Excessive ROS production that exceeds critical levels can overcome all the heart's antioxidants' protection strategy, causing oxidative stress that damages the biological tissues in the hearts [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported by Robertson et al, (2004); Goyal and Patel, (2011) that the cytotoxic action of alloxan is mediated by the formation of free radicals such as superoxide and catalase radicals, which selectively damages the β cells of the pancreas, which are known to be one of the weakest structures to oxidative stress by generating excess reactive oxygen species and produces heart lesions that are similar to human diabetic cardiomyopathy [29]. Excessive ROS production that exceeds critical levels can overcome all the heart's antioxidants' protection strategy, causing oxidative stress that damages the biological tissues in the hearts [29]. In the present study, diabetic control group showed a marked increase in cTnI concentration indicating that there is an extensive damage to the cardiac tissues in the presence of alloxan.…”
Section: Discussionmentioning
confidence: 99%
“…Alloxan and STZ are experimental chemicals that are extensively used to induce hyperglycemic states in animal models. Alloxan has also been reported to induce cardiotoxicity associated with hyperglycemia [16] . Alloxan is chemically stable at acidic pH, supporting its viability as an oral dosage; however, rapid degradation occurs near a physiological pH of 7.4.…”
Section: Discussionmentioning
confidence: 99%